Corneal collagen cross-linking for management of keratoconus in patients affected by Tourette syndrome. Issue 5 (September 2021) - Knutsson, Karl Anders; Paganoni, Giorgio; Ambrosio, Oriella; Ferrari, Giulio; Rama, Paolo
Purpose: To present a series of two patients affected by Tourette syndrome (TS) and progressive keratoconus. Case series: Two young male patients with keratoconus and TS were referred to our center. In both patients eye rubbing was present and in one patient, an ocular tic was present determining blepharospasm. Progression of keratoconus occurred in both cases and corneal collagen cross-linking (CXL) was performed. All treated eyes showed topographic stability with stable refraction and conserved visual acuity, with a follow-up period ranging from 1.5 to 2.5 years. Conclusion: Patients with keratoconus and TS should be observed frequently to document topographical and refractive changes, and in case of progressing disease, CXL should be performed in order to prevent further progression.